A comprehensive numerical study on multi-criteria design analyses in a novel form (conical) of double pipe heat exchanger. (5th June 2016) - Hashemian, Mehran; Jafarmadar, Samad; Sadighi Dizaji, Hamed
Highlights: Conical tube is introduced instead of common cylindrical tube for double pipe heat exchanger. Different configurations of conical tubes are considered in all conditions. Multi-criteria design analyses are done for novel improved geometry. Reasonable results and simple manufacturing makes new model practical. Abstract: In this paper, conical tube was employed instead of cylindrical tube as a novel improved geometry for double pipe heat exchangers. Additionally, various conical tube arrangements with different flow directions (cold or hot flow from big side to small side and vice versa) were investigated. Totally, 3-D model of conical double pipe heat exchanger (CDPHE) has been numerically probed for nine cases. A comprehensive study was performed in order to analyze the effect of hydraulic, geometrical and thermodynamic characteristics in presented heat exchanger. Entropy generation, entropy generation number, heat exchanger reversibility norm (HERN), heat transfer improvement number and effectiveness–NTU (number of transfers unit) are the important concepts which were considered for each nine cases. The results show 55% and 40% increment in effectiveness and heat transfer improvement number at the optimum condition.